Peningkatan Kualitas Layanan Berbasis Growth Mindset pada Guru PAUD - Wulandari, Dian (Journal of Dedicators Community, 2024)
This Community Service aims to improve the quality of PAUD teacher services through strengthening the growth mindset. Excellent service quality is a mainstay for the sustainability of private PAUD which must continue to be improved so that public trust is maintained. The lack of knowledge regarding service components that need to be managed strategically is a problem in improving service quality. This community service activity was carried out at PAUD Gandaria, North Bogor. The activity began with an FGD mapping school conditions, objective reflection, a growth mindset and service quality workshop, identification and elaboration of the potential of the school environment, strengthening commitment to improving services, ending with practices for improving service quality. The result of the activity is strengthening openness of perspective and improving service quality.